Crisis in Nigerian Education: The Bane of Poor Scientific Discovery and National Underdevelopment - Umezurike J. Ezugwu; Sotonye Big-Alabo (PT FORMOSA CENDEKIA GLOBAL, 2023)
In Nigeria, education, which is supposed to be the bedrock of development and harmonious integration, is encumbered with myriads of problems, which include poor funding, politicisation of education, incessant strikes, poor policy implementation, and poorly equipped libraries and laboratories. The outlined aberrations have caused economic meltdown, social unrest, and untold hardship and have continued to discourage scientific discoveries in Nigeria. This paper demonstrates that the non-performing attitude to work that is noticeable in Nigeria's educational system today, is due to the government’s insensitivity towards the highlighted problems above. Furthermore, the paper attempts a resolution of these problems within the framework of complementarism, a relational and inclusive methodology. Under this ambit or framework, a clearer picture is made to show that the crises and problems in education we are dealing with have something to do with us (academia, students, and government), personally and collectively. In the end, the paper shall outline the effects and factors responsible for the disharmonies in the field of Nigerian education and proffer a viable solution